Pengaruh Penambahan Karagenan Terhadap Karakteristik Permen Jeli Salak Bali Varietas Nangka (Salacca zalacca Var. amboinensis) - Widyaningrat, Ayu Kade Eka; Yusasrini, Ni Luh Ari; Puspawati, Ni Nyoman (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 14 No 2 (2025): Jurnal ITEPADO - 10.24843/itepa.2025.v14.i02.p06, 2025)
Jelly candy was a sweet food product made from a mixture of basic ingredients such as sugar, glucose syrup, and water, and was added with thickening agents such as gelatin, pectin, or carrageenan to give a chewy texture. The use of gelatin in jelly candy tended to form a gel that was less firm, and if used in excessive amounts, it resulted in a hard texture. Therefore, a combination of carrageenan was needed to provide a firmer and more elastic texture to the jelly candy. Snake fruit was a fruit whose juice could be used to make jelly candy using carrageenan as a gelling agent. This research aimed to determine the effect of adding carrageenan on the characteristics of nangka variety salak bali jelly candy and to determine the appropriate amount of carrageenan to produce jelly candy with the best characteristics. This study used a Complete Randomized Design with the treatment of adding carrageenan consisting of 6 levels: 0%, 1%, 1.5%, 2%, 2.5%, and 3%. The data obtained were analyzed using variance analysis and parameters that influenced the treatment were followed by Duncan Multiple Range Test (DMRT). The results showed that the addition of carrageenan significantly affected the moisture content, ash, reducing sugar, vitamin C, antioxidant activity, chewiness, sensory aroma, texture, flavor, and overall acceptance of jelly candy. The best treatment was obtained at the addition of 2.5% carrageenan with characteristics of moisture content of 30.77%, ash 0.46%, reducing sugar 20.64%, vitamin C 10.85 mg/100g, antioxidant activity 25.30%, chewiness 0.10 N, with sensory color, aroma, taste slightly liked, texture slightly chewy and slightly liked, and overall acceptance slightly liked. Keywords: snake fruit, carrageenan, jeli candy